Evaluación clínica sobre la infusión anestésica flk (fentanilo, lidocaína, ketamina) para el manejo del dolor intraoperatorio en caninos. - Leones Andrade, Cristhian Abel (Machala : Universidad Técnica de Machala, 2022)
Anesthesiology is understood as one more branch of Veterinary Sciences which is responsible for allowing the performance of surgical processes or treatments that can be painful or annoying and that in some way would be impossible to perform them with the patient in a conscious state, through the fulfillment of 3 fundamental pillars such as: hypnosis, muscle relaxation, analgesia and currently manages the protection of the central nervous system. Pain is described as an unpleasant sensory experience resulting from tissue damage, in animals, it is related to the mechanisms of transduction, transmission, modulation and perception of such harmful stimuli, similar to those already described in humans, continuous anesthetic infusions are one of the tools used, infusions based on morphine, lidocaine and ketamine (MLK), or fentanyl, ketamine and lidocaine (FLK), at analgesic doses have allowed not only to grant adequate analgesia to the surgical process performed, but also in the reduction of the anesthesia required for the patient, subjecting his body to less stress and facilitating his recovery, hence the importance and general objective of this research was to evaluate the effect of the anesthetic infusion of fentanyl, lidocaine and ketamine on the physiological constants related to intraoperative pain in canines. This was a prospective, non-experimental, observational, comparative research, where the effect of an anesthetic FLK infusion on the physiological constants related to intraoperative pain was evaluated, through monitoring and recording of variables such as: heart rate, respiratory rate, mean arterial pressure, temperature and oxygen saturation. The sample consisted of 15 female canine patients, between 6 months and 8 years of age, without weight or race restriction and with an anesthetic risk ASA I or ASA II, subjected to elective ovariohysterectomy and who were treated at the UTMACH veterinary clinic, who underwent the respective clinical history, physical examination and blood counts as part of the preoperative protocol. On the day of the surgery, the patients should have completed 6 hours of fasting, in addition to having a shirt, blanket and necklace. The 15 patients were divided into 3 groups with different intrachirugic analgesia protocols: Fentanyl boluses at regular intervals; infusion of fentanyl, lidocaine and ketamine; infusion of ketamine (0.6mg/kg/h) and lidocaine (1mg/kg/h). Data were recorded of the constants to be studied before the surgical procedure, and at the beginning with the analgesic therapy administered, data were recorded manually in a registry with intervals of 5 minutes, the data obtained were analyzed using the statistical program IMB SPSS version 21, the statistical test performed was ANOVA of a factor looking for significant differences between the study groups, in addition to the Duncan statistical test in those groups whose Sig. value was less than or equal to 0.05, thus rejecting the hypothesis of equality of means. The results obtained showed that there were significant differences between the means of each variable compared to the three groups of anesthetic protocol; patients who were administered fentanyl at regular intervals obtained a decrease in respiratory activity, along with temperature, while patients who were given the FLK infusion showed a normal distribution of physiological constants in relation to the first group, as did patients who received the infusion of ketamine plus lidocaine, with the particularity that this group presented values higher than those obtained in the FLK group, but did not present clinical relevance during surgery. In conclusion, the FLK anesthetic infusion did not present alterations that decreased the activity of the cardiovascular and respiratory system, maintaining stable values with a good therapeutic margin for the management of intraoperative pain in canine female patients undergoing ovariohysterectomy by medial approach.
La Anestesiología es comprendida como una rama más de las Ciencias Veterinarias la cual es encargada de permitir la realización de procesos quirúrgicos o tratamientos que pueden resultar dolorosos o molestos y que de alguna manera sería imposible realizarlos con el paciente en un estado consciente, mediante el cumplimiento de 3 pilares fundamentales como son: la hipnosis, relajación muscular, analgesia y actualmente se maneja la protección del sistema nervioso central. El dolor es descrito como una experiencia sensorial desagradable consecuencia de un daño tisular. En los animales, está relacionada a los mecanismos de transducción, transmisión, modulación y percepción de dichos estímulos nocivos, similar a los descritos en los seres humanos. Las infusiones continuas anestésicas son uno de las herramientas empleadas en procedimientos quirúrgicos, infusiones a base de morfina, lidocaína y ketamina (MLK), o fentanilo, ketamina y lidocaína (FLK), los mismos que han permitido no solo otorgar una analgesia adecuada al proceso quirúrgico realizado, sino también la disminución de anestesia requerida para el paciente, sometiendo a menos estrés su organismo y facilitando su recuperación, de ahí, la importancia. El objetivo general de esta investigación fue evaluar el efecto de la infusión anestésica de fentanilo, lidocaína y ketamina sobre las constantes fisiológicas relacionadas con el dolor intraoperatorio en caninos. La investigación realizada fue prospectiva, no experimental, observacional, comparativa, donde se evaluó el efecto de una infusión anestésica FLK sobre las constantes fisiológicas relacionadas con el dolor intraoperatorio, mediante el monitoreo y registros de variables como: frecuencia cardiaca, frecuencia respiratoria, presión arterial media, temperatura y saturación de oxígeno. La muestra consistió en 15 pacientes caninas hembras, entre 6 meses y 8 años de edad, sin restricción de peso ni raza y con un riesgo anestésico ASA I o ASA II, sometidas a ovario histerectomía electiva y que fueron atendidas en la clínica veterinaria UTMACH, A las mascotas se les realizó la respectiva historia clínica, examen físico y hemogramas como parte del protocolo preoperatorio. El día de la cirugía los pacientes debieron haber cumplido el ayuno adecuado, y su presentación a la clínica con la debida anticipación. Las 15 pacientes fueron divididas en 3 grupos con distintos protocolos de analgesia intraquirúrgico: Bolos de fentanilo a intervalos regulares; infusión continua de fentanilo, lidocaína y ketamina; infusión de ketamina y lidocaína. Se registraron datos de las constantes a estudiar antes del procedimiento quirúrgico, y al inicio con la terapia analgésica administrada, se registraron datos de forma manual en un registro con intervalos de 5 minutos. Los datos obtenidos fueron analizados mediante el programa estadístico IMB SPSS versión 21, la prueba estadística realizada fue ANOVA de un factor buscando diferencias significativas entre los grupos de estudio, además de la prueba estadística Duncan en aquellos grupos cuyo valor de Sig., fue menor o igual a 0.05, rechazando así la hipótesis de igualdad de medias. Los resultados obtenidos demostraron que sí hubo diferencias significativas entre las medias de cada variable en comparación con los tres grupos de protocolo anestésico. Las pacientes que se les administró fentanilo a intervalos regulares, obtuvieron disminución respiratoria, igual la temperatura, mientras que las pacientes que se les administró la infusión FLK mostraron una distribución normal de las constantes fisiológicas en relación al primer grupo, al igual que los pacientes que recibieron la infusión de ketamina más lidocaína, con la particularidad que este grupo presentó valores superiores a los obtenidos en el grupo FLK, mas no presentó relevancia clínica durante la cirugía. Como conclusión, la infusión anestésica FLK no presentó alteraciones en el sistema cardiovascular y respiratorio, manteniendo valores estables con un buen margen terapéutico para el manejo del dolor intraoperatorio en hembras caninas sometidas a ovario histerectomía.
Keywords: MANEJO DEL DOLOR; INFUSION CONTINUA; FLK; OVARIOHISTERECTOMIA